Infrastructure for Growth and Human Development in Pakistan : A Simulation Analysis of Fiscal Policy Options - Kinnunen, Jouko; Lofgren, Hans (World Bank, Washington, DC, 2013)
This paper explores the use of fiscal policy to accelerate development in Pakistan during the period 2013-2022, with a focus on the creation of fiscal space for increased investment in infrastructure, as well as on indicators related to macro and sectoral developments, Millennium Development Goals (MDGs), and education. In terms of method, the analysis relies on simulations with a Pakistani version of MAMS (Maquette for MDG Simulations), a Computable General Equilibrium model developed at the World Bank for country strategy analysis. The different policy scenarios point to the importance of selecting infrastructure projects with high productivity effects and the crucial role of financing in determining the net effects of expanded government infrastructure spending. Transfer programs can generate immediate welfare gains but are less effective over time unless they are designed to raise productivity, perhaps via improvements in health, nutrition, and education outcomes. A final high-growth scenario explores requirements and consequences for Pakistan's economy if, during the period 2013-2022, it managed to raise its rate of annual GDP growth from the 4-5 percent range to 7 percent. The results for the final scenario indicate that rapid growth acceleration may be achieved via a combination of strong increases in savings, investment and total factor productivity. By 2022, 10 years of growth at a rate of 7 percent would spread across the macro demand indicators as well as the major production sectors. Its effects would include significant, broader gains in terms of poverty reduction and better outcomes for indicators.